2022
DOI: 10.1007/s10712-022-09733-0
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Polar Motion Forecast Based on the Holt-Winters Algorithm and Angular Momenta of Global Surficial Geophysical Fluids

Abstract: By taking into account the variable free polar motion (PM) known as the Chandler wobble (CW) and irregular forced PM excited by quasi-periodic changes in atmosphere, oceans and land water (described by the data of effective angular momenta EAM), we propose a short-term PM forecast method based on the Holt-Winters (HW) additive algorithm (termed as the HW-VCW method, with VCW denoting variable CW). In this method, the variable CW period is determined by minimizing the differences between PM observations and EAM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 57 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…This is the last stage which shows that the modeling results of the six stocks affiliated with Israel using the non-seasonal Holt-Winters method can be categorized as very good. From this result, it can provide good forecasting results for some time to come, especially in the context of adjusting the Holt-Winters method is more suitable for short-term forecasting (Luo et al, 2022). For this reason, in this study, log return forecasting is carried out for the next 5 days for the six stocks.…”
Section: Figure 1 : Plot Of Closing Stock Prices Of 6 Company Stocksmentioning
confidence: 99%
“…This is the last stage which shows that the modeling results of the six stocks affiliated with Israel using the non-seasonal Holt-Winters method can be categorized as very good. From this result, it can provide good forecasting results for some time to come, especially in the context of adjusting the Holt-Winters method is more suitable for short-term forecasting (Luo et al, 2022). For this reason, in this study, log return forecasting is carried out for the next 5 days for the six stocks.…”
Section: Figure 1 : Plot Of Closing Stock Prices Of 6 Company Stocksmentioning
confidence: 99%
“…The data for this study were taken from the IERS, which publishes the IERS 14C04 series and forecast product Bulletin-A. Among them, the IERS 14C04 PM data are used as the truth reference to test proposed method (Luo et al 2022), Bulletin-A is used as one of the comparison method. The PMX and PMY series from January 6, 2002 to January 1, 2021, were chosen as experimental data.…”
Section: Datasetsmentioning
confidence: 99%
“…Furthermore, only AAM is used, which is essentially one type of the effective angular momentum (EAM) functions (Barnes et al., 1983). It is shown that oceanic angular momentum (OAM), hydrological angular momentum (HAM), and sea level angular momentum (SLAM) can have a nonnegligible effect on polar motion and dUT1 as well (Bizouard & Seoane, 2010; Brzezinski & Nastula, 2002; Chin et al., 2004; Dahlen, 1976; Dill & Dobslaw, 2010; Dobslaw et al., 2010; Gross, 2008; Kiani Shahvandi, Schartner, & Soja, 2022; Luo et al., 2022; Nastula & Ponte, 1999). Furthermore, phenomena such as El Niño Southern Oscillation (ENSO) can have some influence on the rate of dUT1 (Raut et al., 2022; Xu et al., 2022).…”
Section: Introductionmentioning
confidence: 99%